Pemenuhan Standar Mutu Layanan Kesehatan di Puskesmas Kecamatan Tebing Syahbandar - Fadzlikaselly Widyapuspa Handayani Nugroho; Febri Yuanda; Siti Nur Hasanah; Zidratul Gemilang Ahmad; Dewi Agustina (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2023)
Puskesmas as one of the most important health services infrastructure has a task for give health services to the whole of society. Puskesmas is accused to always keep patient’s trust and satisfaction by give quality services. Quality services in the context of the services at Puskesmas mean give services to the patient based on standard quality for fill up necessary and anxiety of the society, so that they can get satisfaction which finally can increase patient’s trust to Puskesmas. This study aims to determine the quality of health services, the causal factors, and the demands and needs of the community. Measurements from service quality using the SERQUAL method and data extraction is done either quantitatively or qualitatively.